A study on the shifting trends from the traditional joint venture to virtual networks - Ang, Yinghui (2008)
American academic Kathryn R. Harrigan has noted a shifting trend from the traditional joint venture model to one that is based on virtual alliances in America. This exploratory study seeks to find out if the occurrence of the virtual alliance network is happening here in Singapore.